Effectiveness Of Child Protection Law In Fulfilling The Right To Child Custody (Hadhanah) In Kudus Indonesia - Ngazizah, Inna Fauziatal; Yawaee, Hamdan; Abdillah, Kudrat; Abidin, Muhammad Zainal (Fakultas Hukum Universitas Islam Indonesia, 2025)
The protection of children's rights is a fundamental aspect in the Indonesian legal system, as stipulated in Law Number 23 of 2002 concerning Child Protection. In this context, the fulfillment of child custody (hadhanah) is one of the crucial issues to be studied, especially in areas that have complex social and cultural dynamics such as Kudus Regency Indonesia. This study aims to analyze the effectiveness of legal implementation in ensuring the fulfillment of child custody in the region. Using legal research methods and qualitative approaches, data was obtained through structured interviews with 15 informants spread across 9 sub-districts in Kudus Regency Indonesia. The results of the study show that there is still a significant gap between the applicable legal norms and the reality in the field. Various cases of violence against children, economic exploitation, and neglect of basic rights such as access to education and health are still often found. Some of the factors that affect the effectiveness of child protection include low public awareness of the importance of children's rights, the lack of active role of local governments, and the limited family economy which has implications for the neglect of children's rights. Therefore, this study recommends increasing the intensity of legal socialization to the community, strengthening the role of child protection institutions, and optimizing child protection policies that are preventive and responsive. These findings are expected to be strategic considerations for policymakers, legal practitioners, and the wider community in strengthening the child protection system comprehensively in Kudus Regency Indonesia.Keywords: Child protection, children's rights, effectiveness, Kudus Regency. AbstrakPerlindungan hak anak merupakan aspek fundamental dalam sistem hukum Indonesia, sebagaimana yang diatur dalam Undang-Undang Nomor 23 Tahun 2002 tentang Perlindungan Anak. Dalam konteks ini, pemenuhan hak asuh anak ( hadhanah ) menjadi salah satu isu krusial yang menarik untuk dikaji, terutama di daerah dengan dinamika sosial dan budaya yang kompleks seperti Kabupaten Kudus, Indonesia. Penelitian ini bertujuan untuk menganalisis efektivitas implementasi hukum dalam menjamin pemenuhan hak asuh anak di wilayah tersebut. Dengan menggunakan metode penelitian hukum dan pendekatan kualitatif, data diperoleh melalui wawancara terstruktur dengan 15 informan yang tersebar di 9 kecamatan di Kabupaten Kudus, Indonesia. Hasil penelitian menunjukkan bahwa masih terdapat kesenjangan yang cukup signifikan antara norma hukum yang berlaku dengan kenyataan di lapangan. Berbagai kasus kekerasan terhadap anak, eksploitasi ekonomi dan pengabaian hak-hak dasar seperti akses pendidikan dan kesehatan masih sering ditemukan. Beberapa faktor yang mempengaruhi efektivitas perlindungan anak antara lain rendahnya kesadaran masyarakat akan pentingnya hak anak, minimnya peran aktif pemerintah daerah, dan terbatasnya perekonomian keluarga yang berimplikasi pada pengabaian hak anak. Oleh karena itu, penelitian ini merekomendasikan peningkatan intensitas sosialisasi hukum kepada masyarakat, penguatan peran lembaga perlindungan anak, dan optimalisasi kebijakan perlindungan anak yang bersifat preventif dan responsif. Temuan ini diharapkan dapat menjadi pertimbangan strategis bagi para pembuat kebijakan, praktisi hukum, dan masyarakat luas dalam memperkuat sistem perlindungan anak secara komprehensif di Kabupaten Kudus, Indonesia.Kata Kunci: Perlindungan anak, hak anak, efektivitas, Kabupaten Kudus.